Improve acceptance of water reuse: guidelines for planners, investors, project designers and operators - International Water Management Institute (International Water Management Institute, 2023)
As water scarcity worsens across the Middle East and North Africa (MENA), public acceptance of water reuse has become a critical challenge and opportunity. This IWMI thematic brief highlights that barriers ranging from health and environmental concerns to cultural, religious, and economic factors can delay or derail water reuse adoption. Acceptance is driven by trust, knowledge, affordability, risk perception, and the availability of alternatives. Drawing from examples like Deir Debwan in Palestine, where severe shortages have increased support for reuse, the brief emphasizes the need for early, continuous stakeholder engagement and transparent communication. Effective messaging, sensitive to language and cultural context, along with participatory planning and proactive risk communication, can shift public perception. Strategies include avoiding negative terminology (e.g., "wastewater"), using advisory councils, hosting public site visits, and communicating clearly about health safeguards. By equipping planners, policymakers, and utility operators with tailored communication tools and engagement strategies, IWMI underscores the role of trust-building in scaling sustainable water reuse solutions essential to food security and urban resilience in the MENA region.